2019
DOI: 10.1038/s41598-019-48071-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of CLIFAHDD and IHPRF pathogenic variants of the NALCN channel in neuronal cells reveals both gain- and loss-of-function properties

Abstract: The excitability of neurons is tightly dependent on their ion channel repertoire. Among these channels, the leak sodium channel NALCN plays a crucial role in the maintenance of the resting membrane potential. Importantly, NALCN mutations lead to complex neurodevelopmental syndromes, including infantile hypotonia with psychomotor retardation and characteristic facies (IHPRF) and congenital contractures of limbs and face, hypotonia and developmental delay (CLIFAHDD), which are recessively and dominantly inherite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 56 publications
7
43
0
Order By: Relevance
“…These observations indicate that the auxiliary subunits are essential for a functional NALCN ( Supplementary Fig. 1a), consistent with previous studies 30,31 . The electrophysiological properties of NALCN suggested that it tends to maintain the RMP in a manner reminiscent the Le Chatelier's principle in chemical equilibria.…”
Section: Functional Characterization Of Nalcn By Electrophysiologysupporting
confidence: 92%
See 2 more Smart Citations
“…These observations indicate that the auxiliary subunits are essential for a functional NALCN ( Supplementary Fig. 1a), consistent with previous studies 30,31 . The electrophysiological properties of NALCN suggested that it tends to maintain the RMP in a manner reminiscent the Le Chatelier's principle in chemical equilibria.…”
Section: Functional Characterization Of Nalcn By Electrophysiologysupporting
confidence: 92%
“…Despite its physiological and pathological importance, the biophysical properties of the voltage sensitivity and ion selectivity of NALCN are still under debate. Electrophysiological studies on NALCN have been performed in heterologous expression systems such as HEK293 cells, X. laevis oocytes and the neuronal cell line NG108-15 5,30,31 . NALCN expressed in HEK293 cells was reported to exhibit a linear current-voltage relationship, suggesting that NALCN is a voltage-independent ion channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UNC79 and UNC80 are widely expressed in the brain, where they form a complex with NALCN and regulate its localization and function (5,11,34). While UNC79 is not absolutely required for NALCN activity in mouse hippocampal neurons [NALCN-like currents were observed in the absence of UNC79 (5)], both proteins are needed for NALCN function in Drosophila (34), the neuronal cell line NG108-15 (30), HEK-293T cells, and X. laevis oocytes ( Fig. 1 and fig.…”
Section: Unc79 Unc80 and Fam155a Are Crucial For Nalcn Functionmentioning
confidence: 99%
“…UNC79 and UNC80 are widely expressed in the brain, where they form a complex with NALCN and regulate its localisation and function (Yeh et al, 2008, Lu et al, 2010, Lear et al, 2013. While UNC79 is not absolutely required for NALCN activity in mouse hippocampal neurons (NALCN-like currents were observed in the absence of UNC79 (Lu et al, 2010)), both proteins are needed for NALCN function in Drosophila (Lear et al, 2013), the neuronal cell line NG108-15 (Bouasse et al, 2019), HEK293 cells and Xenopus laevis oocytes (Figures 1 and S1), highlighting potential interspecies differences in the regulatory roles of these proteins. FAM155A is pivotal for the axonal localisation of NALCN in C. elegans (Xie et al, 2013).…”
Section: Unc79 Unc80 and Fam155a Are Crucial For Nalcn Functionmentioning
confidence: 99%